Knee osteoarthritis and time-to all-cause mortality in six community-based cohorts: an international meta-analysis of individual participant-level data - Leyland, KM; Gates, LS; Sanchez, M; Nevitt, M; Felson, D; Jones, G; Jordan, JM; Judge, A; Prieto Alhambra, D; Yoshimura, N; Newton, J; Callahan, LF; et al. (Springer, 2021)
Background: Osteoarthritis (OA) is a chronic joint disease, with increasing global burden of disability and healthcare utilisation. Recent meta-analyses have shown a range of effects of OA on mortality, reflecting different OA definitions and study methods. We seek to overcome limitations introduced when using aggregate results by gathering individual participant-level data (IPD) from international observational studies and standardising methods to determine the association of knee OA with mortality in the general population. Methods: Seven community-based cohorts were identified containing knee OA-related pain, radiographs and time-to-mortality, six of which were available for analysis. A two-stage IPD meta-analysis framework was applied: 1) Cox proportional hazard models assessed time-to-mortality of participants with radiographic OA (ROA), OA-related pain (POA), and a combination of pain and ROA (PROA) against pain and ROA-free participants; 2) hazard ratios (HR) were then pooled using the Hartung-Knapp modification for random effects meta-analysis. Findings: 10,723 participants in six cohorts from four countries were included in the analyses. Multivariable models (adjusting for age, sex, race, BMI, smoking, alcohol consumption, cardiovascular disease and diabetes) showed a pooled HR, compared to pain and ROA-free participants, of 1·03 (0·83, 1·28) for ROA, 1·35 (1·12, 1·63) for POA, and 1·37 (1·22, 1·54) for PROA. Discussion: Participants with POA or PROA had a 35 to 37% increased association with reduced time-to-mortality, independent of confounders. ROA showed no association with mortality, suggesting that OA-related knee pain may be driving the association with time-to-mortality. Funding: Versus Arthritis Centre for Sport, Exercise and Osteoarthritis and Osteoarthritis Research Society International